Design and development of disinfecting robot for academic institutions - Puspita, Afrin Hossain; Saad, Riyan Rahman; Faisal, Asif; Tahsin, Namira (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.